Chronische zervikale vagale Stimulation: Mechanismen und momentaner klinischer Stellenwert bei der Herzinsuffizienz = Chronic cervical vagal stimulation : mechanisms of action and clinical relevance for heart failure - Kuschyk, Jürgen; Dösch, Christina; Akın, Ibrahim; Borggrefe, Martin; Röger, Susanne (Herz, 2015)
Increased sympathetic nerve activity and reduced vagal activity are associated with increased mortality in patients after myocardial infarction and patients with chronic heart failure; furthermore, vagal withdrawal has been documented to precede acute decompensation. Experimental studies have indicated that increased parasympathetic activity by means of vagal stimulation may reduce mortality in animal models of postinfarction sudden cardiac death and of chronic heart failure. First clinical results have demonstrated that chronic vagus nerve stimulation in heart failure patients with severe systolic dysfunction appears to be safe and tolerable and may improve the quality of life and left ventricular (LV) function. Vagus nerve stimulation gives rise to these potential clinical benefits by multiple mechanisms of action, including reduced heart rate, restoration of heart rate variability and baroreflex sensitivity, suppression of proinflammatory cytokines and antiarrhythmic effects. First clinical results suggest that vagal nerve stimulation is safe and tolerable and could lead to a marked clinical improvement but discrepancies in the findings due to different study designs warrant further discussion.